Stakeholders’ Roles in Evolutionizing Education: An Evolutionary-Based Toolkit Surrounding Elementary Education - Kathryne Gruskin; Mariah Griffin; Sonaskshi Bansal; Stephanie Dickinson-Frevola; Ashlee Dykeman; Desiree Groce-Volinski; Keydy Henriquez; Maya Kardas; Aileen McCarthy; Aman Shetty; Brandon Staccio; Glenn Geher; et al. (Behavioral Sciences)
There is a rapidly growing body of research in the field of evolutionary educational psychology that examines children’s evolved motivational and educational inclinations as they relate to modern learning and schooling. It is generally agreed that schools are inherently mismatched with how children of our species evolved to learn, thereby contributing to difficulty learning and associated adverse schooling outcomes. Many researchers argue that, by making small changes to schools that help to better align instructional methods and childhood as a whole with our species’ evolved learning mechanisms, we can lessen the negative impacts from evolutionary mismatch and create better outcomes for modern students. In order to create effective change, there must be collaborative work done by parents, teachers, and school administrators. This paper delineates the roles of these stakeholders in elementary education with respect to creating more evolutionarily relevant systems. A research-based toolkit is proposed to guide these stakeholders in evolutionizing the elementary education system.